Pathogen Filtration: An Untapped Ecosystem Service - Klohmann, C. A.; Padilla-Gamiño, J. L. (Frontiers in Marine Science, 2022)
Marine pathogens present serious challenges to aquaculture, fisheries productivity, and marine conservation requiring novel solutions to identify, control, and mitigate their effects. Several ecological habitats, such as mangroves and wetlands can recycle wastes and serve as aquatic filtration systems. While nutrient cycling and other ecosystem services of these habitats have been well-studied, their potential to remove pathogens and mechanisms of filtration remain largely unstudied. Here, we review how mangroves, shellfish beds, seagrasses, and artificial filtration systems can reduce pathogen pressure in coastal ecosystems. Mangroves may inhibit bacterial growth through phytochemicals in their leaves and remove viruses through desalination in their roots. Some bivalves remove pathogens by excreting through their pseudofeces and others concentrate pathogens within their tissues. Seagrasses slow flow rates, increase sedimentation rate and may reduce pathogens through allelopathy. Constructed wetlands decrease pathogens through a combination of mechanical, biological, and chemical filtration mechanisms. Protecting and restoring coastal ecosystems is key to maintaining pathogen filtration capacity, benefiting conservation efforts of threatened host populations, and mitigating large disease outbreaks.